A real time image-guided reposition system for the loosed bone graft in orthognathic surgery. Issue 1 (1st January 2021) - Chen, Xiaojun; Li, Yang; Xu, Lu; Sun, Yi; Politis, Constantinus; Jiang, Xiaoyi
Abstract: In traditional orthognathic surgery, the dental splint technique is typically used to assist surgeons to reposition the maxilla or mandible. However, the design and manufacturing of dental splints is time-consuming and labor-intensive, and the templates may not applicable for some complicated cases due to the anatomic intricacies in the maxillofacial region. During recent years, computer-aided navigation technology has been widely used in oral and maxillofacial surgery. However, due to the limitation of current calibration and registration methods, it has been rarely reported for the motion tracking of intraoperative reposition for the loosed bone graft. In this study, a novel surgical navigation system was developed. With the use of this system, not only the surgical saw can be tracked in real-time, but also the loosed bone graft can be navigated under the guidance of the interactive 2D and 3D views until it is aligned with the preoperatively planned position. The phantom experiments validated the feasibility of our surgical navigation system, and the mean error of image-guided reposition was 1.03 ± 0.10 mm, which was significantly more accurate than the mean error of 5.57 ± 1.40 mm based on the non-navigated methods.